2010
DOI: 10.1152/ajpregu.00524.2009
|View full text |Cite
|
Sign up to set email alerts
|

Acute β-adrenergic stimulation does not alter mitochondrial protein synthesis or markers of mitochondrial biogenesis in adult men

Abstract: Exercise-induced expression of peroxisome proliferator-activated receptor gamma coactivator-1alpha (PGC-1alpha) is dramatically inhibited in mice pretreated with a beta-adrenergic receptor (beta-AR) antagonist, suggesting that beta-ARs play an important role in the regulation of skeletal muscle PGC-1alpha expression, and potentially, mitochondrial biogenesis. Accordingly, we hypothesized that acute beta-AR stimulation would induce transcriptional pathways involved in skeletal muscle mitochondrial biogenesis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 64 publications
2
34
0
Order By: Relevance
“…We have taken the approach of measuring mitochondrial protein synthesis with stable isotopic tracers (14,19,20), although other strategies such as mitochondrial membrane phospholipid or mitochondrial DNA synthesis are theoretically possible. One strength of measuring protein synthesis as a measurement of new mitochondria is that it circumvents complications associated with mitochondrial membrane remodeling (i.e., fission and fusion).…”
Section: Why Does This Matter?mentioning
confidence: 99%
“…We have taken the approach of measuring mitochondrial protein synthesis with stable isotopic tracers (14,19,20), although other strategies such as mitochondrial membrane phospholipid or mitochondrial DNA synthesis are theoretically possible. One strength of measuring protein synthesis as a measurement of new mitochondria is that it circumvents complications associated with mitochondrial membrane remodeling (i.e., fission and fusion).…”
Section: Why Does This Matter?mentioning
confidence: 99%
“…It has been demonstrated that the betaadrenoceptor pathway enhances mitochondrial function in human neural stem cells (Chiang 2012). Notwithstanding, betaadrenergic stimulation does not influence the mitochondrial biogenesis in the skeletal muscle in the human (Robinson et al 2010). In summary, the literature data and our results showed that adrenergic input plays an important role in the regulation of the chondriome in mammals, but the receptors and mechanisms involved in these processes differ between cell types and species.…”
Section: Discussionmentioning
confidence: 38%
“…For instance, acute treatment with β-adrenergic blockers has shown to attenuate post-exercise mitochondrial protein synthesis (Robinson et al, 2011), while chronic ingestion during 5 to 8 weeks of intensive endurance training significantly attenuated improvements in VO2max (Marsh et al, 1983;Sable et al, 1982) and the enzyme activities of complex-II, COX and β-3-hydroxyacyl-CoA dehydrogenase (β-HAD) (Svedenhag et al, 1984). Conversely, acute infusion of adrenergic agonist or chronic ingestion of adrenergic blockers of similar dosage to previously mentioned studies (Marsh et al, 1983;Sable et al, 1982;Svedenhag et al, 1984), has also shown to have no effect on PGC-1α expression and mitochondrial protein synthesis following acute exercise (Robinson et al, 2010) or mitochondrial biogenesis following 6 weeks of endurance training (Wolfel et al, 1986). Reasons for these discrepancies are currently unclear but could be a function of experimental methods used (i.e.…”
Section: β-Adrenergic Stimulationmentioning
confidence: 80%
“…These studies support the findings by Puigserver et al (1998) and implicate adrenergic mechanisms in the regulation of PGC-1α and mitochondrial biogenesis. In human models however, the evidence is less clear regarding an adrenergic regulation of PGC-1α (Marsh et al, 1983;Robinson et al, 2011;Robinson et al, 2010;Sable et al, 1982;Svedenhag et al, 1984;Wolfel et al, 1986). For instance, acute treatment with β-adrenergic blockers has shown to attenuate post-exercise mitochondrial protein synthesis (Robinson et al, 2011), while chronic ingestion during 5 to 8 weeks of intensive endurance training significantly attenuated improvements in VO2max (Marsh et al, 1983;Sable et al, 1982) and the enzyme activities of complex-II, COX and β-3-hydroxyacyl-CoA dehydrogenase (β-HAD) (Svedenhag et al, 1984).…”
Section: β-Adrenergic Stimulationmentioning
confidence: 99%
See 1 more Smart Citation